Grounding: A Practice-led Graphic Exploration of Ecofeminism, Wellbeing and Ecological Consciousness for Young Women - Falconer, Tara; Mortensen Steagall, Marcos (Universidade Anhembi Morumbi, 2023)
This article presents an artistic practice-led visual design research project that employs a reflective inquiry methodology to write and design a series of outcomes responding to a rhetoric approach that looks at how a female designer can develop connections to nature and how the design outcomes can empower women to care for themselves and the planet. A vast amount of literature articulates nature's healing powers (Miyazaki, 2018; Hardman, 2020). There is also an emergency in thinkers discussing the connections between environmentalism and feminism, looking into the ways nature and women are similarly deemed inferior by patriarchal structures (Escobar, 2018; Gruen, 1993). This research project aims to bring these two views together, looking into the benefits of appreciating nature as a form of self-care to empower and strengthen young women and subsequently increase a desire to care for the depleting natural world. Therefore, this thesis asks: how can communication design strategies and conventions encourage young women to connect with a dialogical relation with nature, fostering wellbeing and ecological consciousness? The study is positioned as a reflective inquiry, meaning that the research process utilises the researcher's personal experiences and writing, with reflections about action, in action and after action, as well as stories and photographs anonymously retrieved from other young women. These inspired an exploration of handmade collages and a graphic set, which led to the generation of a series of outcomes that seek to empower young women to care for themselves through nature. The project has been influenced by overarching issues facing women and nature but approaches them through optimism and positivity. It seeks to highlight the fact that small changes matter, and activism starts from caring for your life and the lives of others, which is what the final outcomes seek to instill in the lives of young women facing an uncertain future.
Keywords: Design Research; Ecofeminism; Ecological consciousness; Graphic Design; Practice-led research